Cegah Stunting Melalui Pembentukan Kelas Pranikah CAGAR WARGA (Calon Pengantin Bugar Jiwa Raga) - Fitriyani, Fitriyani; Ersila, Wahyu; M, Festy Mahanani; Chabibah, Nur (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
The stunting rate of toddlers in Pasirkratonkramat Village, the Kramatsari Health Center Area’s, is the highest in Pekalongan City in 2022 and shows an increase in the past year. Stunting prevention is effective in the premarital period. However, health services in the Kamaratsari Health Center Area’s are still not optimal because of the ineffective implementation of adolescent posyandu and there are no premarital classes. In addition, the number of teenage marriages in the region is also still high and plays a role in the problem of stunting under five. This PKM aims to improve premarital health services through the establishment of CAGAR WARGA (Calon Pengantin Bugar Jiwa Raga) premarital class in the hope of improving marriage preparation and reducing the number of teenage marriages. The implementation of this premarital class program activity starts from socialization together with partners to provide information about technical activities and targets, then continues with agreements with midwives, cadres, youth representatives to determine the time and place of implementation. Premarital class activities start from premarital screening covering nutritional status, then continue with the provision of nutrition education, physical preparation, mental preparation, spiritual preparation and maturation of marriage age. Evaluation of activities is carried out well and smoothly in each activity. This premarital class program is expected to become a routine program for puskesmas in Pekalongan City in an effort to prevent stunting.